The Motor Cycle Driving Behavior And Traffic Safety (Case of Ujung Batu District, Rokan Hulu Regency) Riau Province - Abdul Kudus Zaini; Intan Ariska (Jurnal Inovasi Teknologi, 2022)
Motorcycles are one of the modes of transportation to be one of the important parts in supporting every activity. Road safety issues are very closely related to traffic because they can cause material losses and fatalities. Factors that influence the rate of dominant accidents are due to human errors and negligence, due to the lack of level of awareness of the behavior of motorists to traffic regulations. The goal is how good motorcycle rider behavior aspects in prioritizing traffic safety in the Ujung Batu Subdistrict area and Measuring how much the attitude of the level of awareness of motorcycle drivers in the Ujung Batu Subdistrict area for traffic safety campaigns so that these results can be recommended solutions to minimize the negative impact that exists. The research method used is quantitative descriptive with data collection done by questionnaires and field observations. The questionnaire was given to 100 respondents. The questionnaire consisted of 25 statements divided into two variables: the completeness of the rider and the motorcyclist's behavior. The research used on the spread of this questionnaire used a Likert. From the results of a study conducted on 100 respondents, there are various different behavioral phonations. Based on the results of a statistical analysis of the respondents' responses, the community in Ujung Batu District, Rokan Hulu Regency, where the highest coefficient value is 0.785 with the level of awareness of motorcyclists, namely 'Motor vehicles are equipped with vehicle license plate numbers.